Perceived Constraints among Dairy Farmers in Eastern India Using Logistic Regression - Yadav, Bhartendu; Singh Maurya, Abhilash; Kumar Srivastava, Ajay; Bhavesh,; Singh Malik, Joginder (Indian Journal of Extension Education, 2025)
The dairy sector plays a crucial role in sustaining rural livelihoods, especially among the small and marginal farmers, by providing food security, nutrition, and a regular source of income. However, these farmers often face a variety of structural and operational constraints that hinder their growth and economic development. This study investigated the key perceived constraints experienced by selected 270 Marginal-Small (MS) dairy farmers of Eastern Uttar Pradesh in the year 2024, selected through multistage stratified purposive-cum-random sampling, using logistic regression analysis. Among these, the high insurance charges emerged as the most severe factor, increasing the odds of constraint by 17 times. The model was well-fitted as indicated by a Hosmer and Lemeshow test value of 0.201 and Nagelkerke R² of 0.326, explaining about 32.6 per cent of variance in constraints faced. The study concludes that targeted policy reforms are needed to address critical bottlenecks in the dairy sector. Overall, the findings reinforce the importance of a need-based and evidence-driven approach for inclusive rural development through dairy enterprise support.
Keywords: Constraints; Farmers; Dairy; Logistic Regression; Rural development; Agriculture